Málsvörn Jóns Ásgeirs Jóhannessonar - Einar Kárason 1955- (Mál og menning, 2021)
Jón Ásgeir Jóhannesson first caught the attention of the Icelandic public when he started the budget supermarket Bónus. It was a sensation in the Icelandic supermarket landscape and very quickly became the largest on the market. That led to further adventures until Jón Ásgeir was a large owner of an Icelandic bank and on the front pages of many an Icelandic magazine in the years before and after the economic crisis.
Keywords: Jón Ásgeir Jóhannesson -- 1968-; Geschichte 1992-2020; Investmentbank; Supermarkt; Finanzkrise; Island; Biografie